2018
DOI: 10.1016/j.resuscitation.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Medical facilities in the neighborhood and incidence of sudden cardiac arrest

Abstract: We did not observe a protective association between medical facilities in the home census tract and SCA risk, orbetween major medical centers in the event census tract and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The NETS data represent a census of all businesses across the United States, and the NETS is considered one of the most comprehensive databases of establishments available. Prior studies 2,23,24 have used the NETS data to examine health care facilities and specific chronic conditions. From the NETS, records were categorized as ambulatory care facilities or as pharmacies and drugstores using SIC codes (eTable 1 in the Supplement).…”
Section: Dependent Variable Of Health Care Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The NETS data represent a census of all businesses across the United States, and the NETS is considered one of the most comprehensive databases of establishments available. Prior studies 2,23,24 have used the NETS data to examine health care facilities and specific chronic conditions. From the NETS, records were categorized as ambulatory care facilities or as pharmacies and drugstores using SIC codes (eTable 1 in the Supplement).…”
Section: Dependent Variable Of Health Care Facilitiesmentioning
confidence: 99%
“…After examining the distribution of counts, CTs were classified as having none vs any for each type of health care facility (ambulatory care facilities or pharmacies and drugstores). Census tracts were divided into the following 4 trajectories of health care facility presence over time between 2000 and 2014: (1) never having any facilities (CTs having none at both time points), (2) losing (CTs going from having at least 1 to having none), (3) gaining (CTs going from having none to having at least 1), and (4) always having a facility (CTs having at least 1 at both time points). geographies and measurements over time.…”
Section: Dependent Variable Of Health Care Facilitiesmentioning
confidence: 99%
“…With respect to the time-to-MI analysis, our study provided further evidence to support previously identified demographic and other risk factor characteristics associated with an increased risk of MI. The lack of a significant association between medical facility exposures and MI events coupled with prior findings (Goh et al, 2018) casts doubt on their salience and may indicate that other neighborhood level amenities and features, or neighborhood features accessible during earlier periods of life, have greater potential for explaining both aging in place and time -to -MI.…”
Section: Resultsmentioning
confidence: 91%
“…We measured medical facilities and other neighborhood level characteristics in 5 km buffers in order to represent a reasonable distance that someone might comfortably travel to seek medical care. It is also thought that the densities of businesses and features in this size buffer can have the greatest potential to affect health, a strategy inspired by Goh et al (2018). Realistically, individuals may travel much closer or farther to seek medical care, and thus our measurement of the density of medical facilities and other features in 5 km radial buffers may not capture care-seeking behavior, thus potentially missing associations that may exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation